Instructional Leadership Practice in Elevating the Quality of Education in Islamic School A Case Study at SMA Muhammadiyah 4 Depok - Istikomah, Istikomah; Iswan, Iswan; Winata, Widia (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2025)
This article aims to scrutinize the practice of instructional leadership implemented by the school principal of SMA Muhammadiyah (SMAM) 4 Depok in advancing the quality of Education. The approach used in this study is qualitative research employing a case study design. Result of this study reveals that the strategy of instructional leadership practiced by the principal of SMAM 4 Depok encompasses the followings: a). Broadening the school vision into more outward looking which integrates Islamic values with national and global curriculum into its instructional programs; b). Managing instructional programs based on periodical basis such as supervision, curriculum coordination, and monitoring students’ progress; and c). Providing appreciation to the best teacher and the excellent student, developing teachers with some professional trainings, and maintaining high visibility entirely both internal and external involvement in building school positive school climate. In a nutshell, the instructional leadership practiced by the principal of SMAM 4 Depok is effectively implemented where Islamic values are systematically internalized. Nonetheless, it is imperative to pay attention to strengthening the instructional programs of global dimension  to enhance the quality of academic outcome (competitive advantage) towards higher level both national and global one.